Pengaruh Desain Kerja dan Efektivitas Kerja Terhadap Kinerja Karyawan (Studi PT. Semen Indonesia Persero Tbk) - Shofiyono, Akhmad Aries (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
The Key Performance Indicator (KPI) method can be used to measure employee performance in a company. Key Performance Indicators for 2019 PT. Semen Indonesia Persero Tbk stil has a high percentage of not meeting the target, which means that there are factors that cause employee performance not be achived. it is suspected that work effectiveness are the cause of the employee’s not achieving performance. In addition, there are still inconsistencies in the results of previous studies with the results. So this thesis is the result of quantitative research that aims to answer the formulation of the problem regarding the effect of work design and work effectiveness on employee performance with a case study at PT. Semen Indonesia Persero Tbk either through partial or simultaneous testing. This research methodology uses quantitative research with causal research type. For the research sample, namely some of the employees of PT. Semen Indonesia Persero Tbk taken according to purposive sampling technique. The testing used is starting from testing the research questionnaire using validity and reliability tests. Furthermore, data analysis begins with the classical assumption test, multiple linier regression, t test, simultaneous test (f test) and the coefficient of determination test. In the testing phase, researchers used SPSS version 25 to test the statistics. The results obtained from the tests that have been carried out obtain the results that work design has no significant effect on employee performance, work effectiveness has a significant effect on employee performance. While the letter, namely simultaneously work design and work effectiveness have a significant effect on the performance of employees of PT. Semen Indonesia Persero Tbk.